Pharmacological evaluation of ethnomedicinal Glycosmis pentaphylla Lour. as antidiabetic, antioxidant and cytotoxic agent - Mohammad Oliur Rahman, Mohammad Badiur Rahman, Shah Alam Siddiqui, Mohammad Abul Hassan, Mohammad Abdur Rashid (Journal of Applied Pharmaceutical Science, 2018)
In this study, an ethnomedicinal plant Glycosmis pentaphylla Lour. has been investigated for its pharmacological potential including antidiabetic, antioxidant, and cytotoxic activities. In the investigation of antidiabetic activity, diabetic induced rats were received methanol extract repeatedly for consecutive 3 weeks. This treatment with the extracts resulted in a reduction of the blood glucose level to 33.82%, 24.38%, and 9.59% after 7, 14, and 21 days of treatment, respectively. In this case, statistically significant blood glucose lowering potential of methanol leaf extract at a dose of 250 mg/kg body weight (bw) was found. In 2,2-diphenyl-1-picrylhydrazyl radical scavenging assessment, moderate antioxidant activity was observed for crude methanol extract with an IC50 value of 46.75 μg/ml. In brine shrimp lethality evaluation, the methanol extract showed significant cytotoxicity with an LC50 value of 22.55 μg/ml. Our study testifies that methanol extract of Glycosmis pentaphylla has promising pharmacological activities and explored these species as a potential source of active secondary metabolites for pharmaceutical and agrochemical industries.
Keywords: Antidiabetic, DPPH, brine shrimp lethality, cytotoxicity, Glycosmis pentaphylla.